Forty Third Meeting of the National Development Council December 23-24, 1991 Summary Record - Planning Commission (Planning Commission, 1991)
Eighth Five Year Plan, he observed that the challenges and opportunities before this august body are well known and it has to provide direction for the future growth of the Nation. He also mentioned that a creative reorientation of our approach to planning was called for in the face of acute resource constraints and imperatives of a higher rate of growth.
Government of India Planning Commission
Government of India Planning Commission